2008
DOI: 10.1007/s11606-008-0510-7
|View full text |Cite
|
Sign up to set email alerts
|

Primary-care Clinician Perceptions of Racial Disparities in Diabetes Care

Abstract: BACKGROUND: Primary-care clinicians can play an important role in reducing racial disparities in diabetes care. OBJECTIVE:The objective of the study is to determine the views of primary-care clinicians regarding racial disparities in diabetes care. DESIGN:The design of the study is through a survey of primary-care clinicians (response rate=86%). PARTICIPANTS:The participants of the study were 115 physicians and 54 nurse practitioners and physician assistants within a multisite group practice in 2007. MEASUREME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 31 publications
(41 reference statements)
1
34
1
Order By: Relevance
“…Sequist et al 4 recommend two strategies to expose health care providers to the issue of racial disparities in diabetes care, including provider feedback regarding disparities as well as cultural competency training to improve communication skills. However, recent data suggest that in the business world, mandatory cultural competency is not efficient, and if anything, potentially detrimental.…”
Section: Published Online April 5 2008mentioning
confidence: 99%
See 2 more Smart Citations
“…Sequist et al 4 recommend two strategies to expose health care providers to the issue of racial disparities in diabetes care, including provider feedback regarding disparities as well as cultural competency training to improve communication skills. However, recent data suggest that in the business world, mandatory cultural competency is not efficient, and if anything, potentially detrimental.…”
Section: Published Online April 5 2008mentioning
confidence: 99%
“…[2][3][4][5] In this editorial, we will attempt to synthesize the results of these studies and make recommendations on how to shape future research to reduce, but preferably to completely eliminate, healthcare disparities. These recommendations should be useful to clinicians, researchers, administrations, and policy makers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 This dominant framing of disparities is also consistent with the views of many providers, who believe that disparities are due mainly to patient factors rather than provider factors. [18][19][20] For example, in a study of primary care clinicians by Sequist et al published in JGIM in 2008, among the 52% who reported that racial disparities in the quality of diabetes care existed in their own health care system, less than 10% attributed these disparities to provider differences in prescribing medications and differences in referral to specialists and about 20% attributed disparities to providers' miscommunication with patients. By contrast, about 40% attributed disparities to patient preferences; 45% to patient attitudes and beliefs about the provider; and over 70% to patient health behaviors.…”
mentioning
confidence: 99%
“…13,14 Indications that providers may be threatened by the existence of racial inequality are findings that, while a sizable percentage of providers do not believe that disparities exist, even fewer acknowledge the existence of disparities in their own practice. [18][19][20]23,24 For example, in a survey of cardiologists, 33%…”
mentioning
confidence: 99%